2005
DOI: 10.1063/1.1938973
|View full text |Cite
|
Sign up to set email alerts
|

Alfvén eigenmodes in reversed shear plasmas in JT-60U negative-ion-based neutral beam injection discharges

Abstract: Rapid frequency sweeping modes observed in reversed magnetic shear (RS) plasmas on the Japan Atomic Energy Research Institute Tokamak 60 Upgrade (JT-60U) [H. Ninomiya and the JT-60 Team, Phys. Fluids B 4, 2070 (1992)] have been identified as reversed-shear-induced Alfvén eigenmodes (RSAEs), which are ideal magnetohydrodynamic Alfvén eigenmodes (AEs) localized to the region of minimum safety factor, qmin, and are excited by negative-ion-based neutral beam injection. The chirping and subsequent saturation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 24 publications
3
60
0
Order By: Relevance
“…Figure 4 illustrates how an n = 1 instability sweeps up through the range 40-90 kHz while another sweeps down through 130-90 kHz over the period from 6-6.5 s, when both merge into a single mode [136]; the mode amplitude is enhanced when the frequency chirping saturates. The kinetic full-wave code TASK/WM has been used to interpret the measurements as reversed shear induced AEs (RSAE, an alternative name for Alfvén cascades) located immediately below the m = 2 and above the m = 3 Alfvén continua merging into a (3,2) TAE where q MIN ∼ = 2.5 [137].…”
Section: Identification Of Alfvénic Modes In Different Operating Scenmentioning
confidence: 99%
“…Figure 4 illustrates how an n = 1 instability sweeps up through the range 40-90 kHz while another sweeps down through 130-90 kHz over the period from 6-6.5 s, when both merge into a single mode [136]; the mode amplitude is enhanced when the frequency chirping saturates. The kinetic full-wave code TASK/WM has been used to interpret the measurements as reversed shear induced AEs (RSAE, an alternative name for Alfvén cascades) located immediately below the m = 2 and above the m = 3 Alfvén continua merging into a (3,2) TAE where q MIN ∼ = 2.5 [137].…”
Section: Identification Of Alfvénic Modes In Different Operating Scenmentioning
confidence: 99%
“…It was demonstrated that MHD theory can explain frequency chirping behavior of so-called Alfvén cascades observed in reversed shear plasmas. [18][19][20] Recently, the ␣ particle driven Alfvén eigenmode observed in the Tokamak fusion test reactor was reexamined and explained in terms of the cylindricallike MHD eigenmode. 21 In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…RSAEs and characteristic frequency sweeping were observed in many tokamaks during ion cyclotron resonance frequency (ICRF) heating and NBI in the current ramp-up phase [23][24][25][26][27][28][29][30][31]. The RSAE frequency is swept unidirectionally, that is, upward from a certain minimum when q min decreases in time from a rational value.…”
Section: Aes In Reversed Magnetic Shear Plasmasmentioning
confidence: 99%
“…In RS tokamak plasmas, characteristic energetic-iondriven modes called RSAEs or Alfvén cascade modes are observed [23][24][25][26][27][28][29][30][31]. Moreover, a GAM having an n = 0 mode structure is sometimes excited by energetic ions [32,33].…”
Section: Aes In Reversed Magnetic Shear Plasmasmentioning
confidence: 99%